MODDING SKYRIM WITH GENERATIVE AI: EXPLORING IMAGINARIES AND PLAYER-NPC INTERACTIONS - Paz, Samyr; Freitas, Camila; Rolim, Gabriela (AoIR Selected Papers of Internet Research, 2026)
Imagine a scenario in which players engage in conversations with non-playable characters (NPCs) in video games using a microphone, free from scripted responses or predefined constraints. With the advancement of Generative Artificial Intelligence (GAI), this possibility has become more feasible than ever. This article examines the Mantella mod for The Elder Scrolls V: Skyrim (Bethesda, 2011), which facilitates natural language interactions with NPCs, transforming player engagement within the game’s fictional universe. Skyrim is an action role-playing game (RPG) developed by Bethesda Game Studios. With over 60 million copies sold and releases spanning three generations of gaming consoles, Skyrim has cemented its place in gaming history. A significant factor contributing to its enduring relevance is its vibrant modding community, which has enabled players to modify and expand the game in myriad ways – ranging from graphical enhancements to the introduction of new areas and survival mechanics. This extensive capacity for customization has sustained the game’s popularity for over a decade since its initial release. The primary objective of this article is to investigate the creative appropriation of GAI by Skyrim’s PC modding community. Specifically, it addresses the following question: What AI imaginaries emerge from Skyrim gameplay influenced by the Mantella mod? To explore this question, 13 YouTube videos were collected using ethnographic techniques, complemented by a formal gameplay analysis.